Variations of the electric field zonal component, the vertical component of the plasma drift and neutral wind velocities in ionosphere over Kharkov (Ukraine) during August 5–6, 2011 and November 13–15, 2012 magnetic storms - Domnin, I. F.; La Hoz, C.; Lyashenko, M. V. (НТУ "ХПІ", 2014)
The modeling results of the zonal electric field and the vertical component of the plasma transfer velocity due to electromagnetic drift during August 5–6, 2011 and November 13 – 15, 2012 magnetic storms were presented. Confirmed that has a penetration of electric fields from magnetospheric origin in the mid-latitude ionosphere during strong geomagnetic disturbances. For the considered disturbed periods the neutral wind parameters were calculated using Kharkov incoherent scatter radar data.

Представлено результати моделювання варіацій зонального електричного поля та вертикальної компоненти швидкості переносу плазми за рахунок електромагнітного дрейфу під час магнітних бур 5–6 серпня 2011 р. та 13–15 листопада 2012 р. Підтверджено, що під час сильних геомагнітних збурень має місце проникнення електричних полів магнітосферного походження у середньоширотну іоносферу. Для розглянутих збурених періодів розраховано параметри нейтрального вітру з використанням даних Харківського радара некогерентного розсіяння.
Keywords: ionosphere; geospace storm; zonal electric field; plasma drift; іоносфера; геокосмічна буря; зональне електричне поле; дрейф плазми